Biosimilar SB11 versus reference ranibizumab in neovascular age-related macular degeneration: 1-year phase III randomised clinical trial outcomes. Issue 3 (16th October 2021) - Bressler, Neil M; Veith, Miroslav; Hamouz, Jan; Ernest, Jan; Zalewski, Dominik; Studnička, Jan; Vajas, Attila; Papp, András; Vogt, Gabor; Luu, James; Matuskova, Veronika; Yoon, Young Hee; et al.
Abstract : Background/Aims: To provide longer-term data on efficacy, safety, immunogenicity and pharmacokinetics (PK) of ranibizumab biosimilar SB11 compared with the reference ranibizumab (RBZ) in patients with neovascular age-related macular degeneration (nAMD). Methods: Setting : Multicentre. Design : Randomised, double-masked, parallel-group, phase III equivalence study. Patient population : ≥50 years old participants with nAMD (n=705), one 'study eye'. Intervention: 1:1 randomisation to monthly intravitreal injection of 0.5 mg SB11 or RBZ. Main outcome measures : Visual efficacy endpoints, safety, immunogenicity and PK up to 52 weeks. Results: Baseline and disease characteristics were comparable between treatment groups. Of 705 randomised participants (SB11: n=351; RBZ: n=354), 634 participants (89.9%; SB11: n=307; RBZ: n=327) completed the study until week 52. Previously reported equivalence in primary efficacy remained stable up to week 52 and were comparable between SB11 and RBZ. The adjusted treatment difference between SB11 and RBZ in full analysis set at week 52 of change from baseline in best-corrected visual acuity was −0.6 letters (90% CI −2.1 to 0.9) and of change from baseline in central subfield thickness was −14.9 µm (95% CI –25.3 to –4.5). The incidence of ocular treatment-emergent adverse events (TEAEs) (SB11: 32.0% vs RBZ: 29.7%) and serious ocular TEAE (SB11: 2.9% vs RBZ: 2.3%) appeared comparable between treatment groups, and no new safety concerns were observed. The PK and immunogenicity profiles were comparable, with a 4.2% and 5.5% cumulative incidence of antidrug antibodies up to week 52 for SB11 and RBZ, respectively. Conclusions: Longer-term results of this study further support the biosimilarity established between SB11 and RBZ.